КӨРКЕМ-ҲҮЖЖЕТЛИ ПОВЕСТЬЛЕРДЕ ТЕМАТИКАЛЫҚ ИЗЛЕНИСЛЕР - Жәримбетова, Т.Қ. (FAN va JAMIYAT, 2022)
The article discusses that in the Karakalpak literature, a fictional documentary story is based primarily on real events, the creation of an image of a living or surviving hero in it, the thematic focus is revealed through events and images.